Sensor behavior of MoS2 field-effect transistor with light injection toward chemical recognition. Issue 43 (3rd August 2021) - Alam, Md Iftekharul; Takaoka, Tsuyoshi; Waizumi, Hiroki; Tanaka, Yudai; Al Mamun, Muhammad Shamim; Ando, Atsushi; Komeda, Tadahiro
Abstract : The application of field-effect transistor (FET) devices with atomically thin channels as sensors has attracted significant attention. We further explore the method to attach the chemical recognition capability by combining with light injection. Abstract : The application of field-effect transistor (FET) devices with atomically thin channels as sensors has attracted significant attention, where the adsorption of atoms/molecules on the channels can be detected by the change in the properties of FET. Thus, to further enhance the chemical sensitivity of FETs, we developed a method to distinguish the chemical properties of adsorbates from the electric behavior of FET devices. Herein, we explored the variation in the FET properties of an MoS2 -FET upon visible light injection and the effect of molecule adsorption for chemical recognition. By injecting light, the drain current ( I d ) increased from the light-off state, which is defined as (Δ I d )ph . We examined this effect using CuPc molecules deposited on the channel. The (Δ I d )ph vs. wavelength continuous spectrum in the visible region showed a peak at the energy for the excitation from the highest occupied orbital (HOMO) to the molecule-induced state (MIS). The energy position and the intensity of this feature showed a sensitive variation with the adsorption of the CuPc molecule and are in good agreement with previously reported photo-absorption spectroscopy data, indicating that this technique can be employed for chemical recognition.